Case series: eruptive xanthomas and hyperlipdaemia - Anaba, Ehiaghe L.; Cole-Adeife, Olufolakemi M.; Oaku, Ruth I. (International Journal of Research in Medical Sciences, 2021)
Eruptive xanthomas are uncommon with only case reports documented making it difficult to have a prevalence figure. These asymptomatic eruptions are usually a clue to an underlying metabolic disorder with associated cardiovascular risk. Early diagnosis and treatment prevent its associated morbidity and mortality. We present a case series of 2 males (29 and 40 years) and 3 females (14, 28 and 40 years old). They presented with lesions clinically consistent with eruptive xanthomas. Laboratory and histologic investigations revealed dyslipidemia and lipid laden macrophages. They were placed on statins with an improvement of skin lesions and improvement in lipid levels. Dermatologists should be aware of skin lesions as a marker of severe dyslipidemia and its attendant cardiovascular risk. Early treatment leads to resolution of xanthomas and prevention of cardiac related morbidity and mortality.